DOGMATISM AND ITS RELATIONSHIP TO IRRATIONAL THOUGHTS FOR STUDENTS OF THE COLLEGE OF PHYSICAL EDUCATION AND SPORTS SCIENCES, THI QAR UNIVERSITY - Assistant Teacher. Ghusoon Hassoon Mohammed (European Journal of Humanities and Educational Advancements, 2023)
It seems that correct flexible thinking is an urgent need that we need at this current time more than ever before. However, the world has become more complex as a result of the challenges imposed by technology, information technology in various aspects of human life, as success in facing these challenges does not depend on the amount of knowledge. As much as it depends on how knowledge is used and applied, intellectual stagnation is one of the dangerous psychological and social phenomena widespread in all Arab and Western societies, and dogmatic individuals are characterized by strictness with those with opposing beliefs without any attempt to identify and think about those ideas, and therefore the dogmatic person is an individual who does not respond appropriately. Due to the characteristics of the cognitive situation, as it falls under the influence of a closed belief system, and dogmatic individuals are among the most angry and aggressive people, and from the above reveals indicators or indications that show the possibility of these people occurring or adopting illogical ideas as a result of their following this cognitive style, and the researcher believes that studying the correlation Intellectual stagnation and irrational thoughts are very important and have a significant impact on the actions of individuals in general and university students in particular since they are at the beginning of their lives and careers and the various circumstances and incidents they may encounter and how they respond to these events and situations. The researcher relied on the descriptive approach in the style of correlational relationships, and the research sample was represented by ( 300 male and female students from the original community were chosen randomly, with (162) male and (138) female students. Two scales of intellectual inertia and a scale of irrational thoughts were used. It was concluded from the results that the relationship between dogmatism and irrational thoughts is a direct, statistically significant relationship. The more dogmatism, the more irrational thoughts, and vice versa. Also, the members of the research sample possessed dogmatism at a moderate rate. The recommendations by the researcher were the necessity of conducting guidance programs on the topics of dogmatism and irrational thoughts and their negative effects on the individual